From New Federalism to Devolution Twenty-Five Years of Intergovernmental Reform. - Conlan, Timothy J. (Brookings Institution Press, 1998)
In the period from 1970 to the early 1990s, Republican leaders launched three major reforms of the federal system. Although all three initiatives advanced decentralization as a goal, they were remarkably different in their policy objectives, philosophical assumptions, patterns of politics, and policy outcomes. Expanding and updating his acclaimed book, New Federalism: Intergovernmental Reform from Nixon to Reagan (1988), Timothy Conlan provides a comprehensive look at intergovernmental reform from Nixon to the 104th Congress. The stated objectives of Republican reformers evolved from rationali.